1986
DOI: 10.1073/pnas.83.10.3262
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the pKa of the bacteriorhodopsin Schiff base by use of artificial retinal analogues.

Abstract: Artificial bacteriorhodopsin pigments based on synthetic retinal analogues carrying an electron-withdrawing CF3 substituent group were prepared. The effects of CF3 on the spectra, photocycles, and Schiff base pKa values of the pigments were analyzed. A reduction of 5 units in the pKa of the Schiff base is observed when the CF3 substituent is located at the C-13 polyene position, in the vicinity of the protonated Schiff base nitrogen. The results lead (D) to the unambiguous characterization of the (direct) titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 27 publications
(34 reference statements)
6
96
0
Order By: Relevance
“…Reconstitution of Arch3 and four ChR variants with A2 retinal, which carries an extra double bond, resulted in functional pigments with enhanced longwavelength sensitivity 29 . Extensive work on bacteriorhodopsin (BR) [45][46][47][48][49] using synthetic retinal analogues suggests that many other retinal analogues, particularly those with ring modifications, might be applicable for the purpose of chromophore substitution. However, in most cases, it was only shown that the absorption maximum was shifted, without analysing the rhodopsin function.…”
mentioning
confidence: 99%
“…Reconstitution of Arch3 and four ChR variants with A2 retinal, which carries an extra double bond, resulted in functional pigments with enhanced longwavelength sensitivity 29 . Extensive work on bacteriorhodopsin (BR) [45][46][47][48][49] using synthetic retinal analogues suggests that many other retinal analogues, particularly those with ring modifications, might be applicable for the purpose of chromophore substitution. However, in most cases, it was only shown that the absorption maximum was shifted, without analysing the rhodopsin function.…”
mentioning
confidence: 99%
“…Thus, a neutral residue at position 85 shifts the pK for SB deprotonation in the dark from -13 (15,16) for wild type to between 7 and 8. These values are close to those reported for SB model compounds in solution (16). The effect of the charge at position 85 on the pK of the SB requires that this residue interacts with and is close to the protonated SB.…”
Section: Discussionmentioning
confidence: 99%
“…pK a calculations were performed using APBS (58) with the setup described above. All titratable residues were sampled using the Monte Carlo procedure in Karlsberg+, for which a benchmarked accuracy of ∼1 pK a unit has been found (59)(60)(61). VMD (62) was used for analysis and visualization.…”
Section: Methodsmentioning
confidence: 99%